MODERN INDIVIDUAL-COMPREHENSIVE APPROACH IN THE TREATMENT OF HEMORHOIDS - M. М. Militsa; M. D. Postolenko; K. M. Militsa; V. V. Soldysova (Сучасні медичні технології)
Objective. The aim of the study was to analyze the effectiveness of modern treatments in 485 patients with chronic hemorrhoids stage II-III-IV over the past 3 years.